Pengetahuan, Sikap dan Perilaku Penggunaan Obat pada Mahasiswa di Jember - Rachmawati, Ema; Astutik, Amelia Windi; Pratama , Antonius Nugraha Widhi (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Abstract: The ease of accessing information about medicines has an impact on increasing the practice of self-medication in the community. However, there are still many irrational self-medication practices, including inappropriate drug selection, not being aware of side effects, or the use of antibiotics for self-medication. Students are a group of people with a higher education level who cannot be separated from the use of medicines for self-medication of the disease they are experiencing. This study aimed to determine the knowledge, attitudes, and behavior of drug use among students in Jember and the factors that influence it. This study was a cross-sectional survey using a questionnaire conducted online in April-May 2020. The research respondents were undergraduate students (diploma and strata-1 students) at several universities in Jember. A total of 544 students became respondents in this study. The majority of respondents (344; 63.2%) had